2004
DOI: 10.1063/1.1724818
|View full text |Cite
|
Sign up to set email alerts
|

Modification of statistical threading in two-component pseudorotaxane melts using the amphiphilic approach and variations in the confinement geometry

Abstract: Recently we described a coarse-grained model of poly(ethylene oxide) and then employed that model to study the amount of spontaneous threading of cyclic molecules by linear chains in the melt [C. A. Helfer, G. Xu, W. L. Mattice, and C. Pugh, Macromolecules 36, 10071 (2003)]. Since the amount of statistical threading at equilibrium is small, there is interest in identifying physical changes in the system that will increase the threading. We now use that coarse-grained model to investigate the effect on threadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, Pugh and co-workers have demonstrated that homopolyrotaxanes are accessible in the laboratory. [30][31][32] Simulations have supported the laboratory synthesis by providing guidance on the optimal size for the cyclic component 26 and influence of the solvent 27 and by providing independent support 28 for the utility of the amphiphilic approach originated by Pugh. 30 Here the simulation method employed for the investigation of the homopolyrotaxanes [26][27][28][29] is used for the study of melts of catenanes in which all components are constructed from PEO.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, Pugh and co-workers have demonstrated that homopolyrotaxanes are accessible in the laboratory. [30][31][32] Simulations have supported the laboratory synthesis by providing guidance on the optimal size for the cyclic component 26 and influence of the solvent 27 and by providing independent support 28 for the utility of the amphiphilic approach originated by Pugh. 30 Here the simulation method employed for the investigation of the homopolyrotaxanes [26][27][28][29] is used for the study of melts of catenanes in which all components are constructed from PEO.…”
Section: Introductionmentioning
confidence: 96%
“…[30][31][32] Simulations have supported the laboratory synthesis by providing guidance on the optimal size for the cyclic component 26 and influence of the solvent 27 and by providing independent support 28 for the utility of the amphiphilic approach originated by Pugh. 30 Here the simulation method employed for the investigation of the homopolyrotaxanes [26][27][28][29] is used for the study of melts of catenanes in which all components are constructed from PEO. The results are compared with similar simulations of melts composed of individual rings that have the same mass as both rings in the catenanes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that threading is favored by aggregation in a poor solvent. In addition, planar alignment can double the extent of threading (to 9% of the rings threaded) compared to the purely statistical threading in the melt, if the distance between cycles in two consecutive layers is confined to a distance approximately equal to the size of the rings 1 Amphiphilic Approach for Synthesizing Polyrotaxanes that Lack an Enthalpic Driving Force for Threading …”
Section: Introductionmentioning
confidence: 99%
“…5 If an added thread is also not soluble in the selective solvent, it will be forced into the interior of the micelle (Scheme 1), where the high concentration and alignment of the macrocycles should promote threading. Although we have not yet mimicked this three-component system using simulations, we have recently used Monte Carlo simulations to investigate both the effect of solvent quality 6 and the alignment 7 of the macrocycles on the extent of threading 42-crown-14 with CH 3 (OCH 2 CH 2 ) 13 -OCH 3 ; we previously found that 42-crown-14 is approximately the optimum ring size for maximum spontaneous threading by PEO with inconsequential multiple threading. 8 Compared to the melt (1.73 threading events ) 4.33% of the rings threaded), 8 the number of threading events decreases with solvent dilution since there are fewer rings present, and the percentage of rings threaded are lower in the good and Θ solvents than in the melt and poor solvent.…”
Section: Introductionmentioning
confidence: 99%